From chronic inflammation to immune escape: mapping the tumor microenvironment evolution in renal cell carcinoma - Xu, Hanjun; Tu, Baojun; Li, Hui; Shan, Yong (Frontiers in Immunology, 2025)
Renal cell carcinoma (RCC) evolves within a chronic inflammatory renal niche, where angiogenesis, metabolism, and immune programs synergize to reshape the tumor immune microenvironment (TIME). Recurrent renal damage and tissue hypoxia sustain NF-κB/STAT3 and HIF-VEGF signaling, while a sustained IFN-γ response enhances antigen presentation while inducing inhibitory checkpoints, promoting a state of “inflammation but constrained.” Single-cell and spatial studies reveal early microenvironment heterogeneity and the chemokine-checkpoint paradox: regions enriched in CXCL9/10 coexist with endothelial inertia, cancer-associated fibroblasts (CAFs)-mediated stromal barriers, and metabolic stress, which collectively exclude functional CD8+T cells. In advanced clear cell RCC, immuno-inflammatory, immuno-excluded, and immuno-desert phenotypes often coexist and undergo transitions during treatment, leading to heterogeneity in response to immune checkpoint blockade (ICB). We propose a modular perspective-the NF-κB/STAT3, HIF-VEGF, IFN-γ circuits and auxiliary regulatory factors-to link stage-specific biology with treatment matching. Integrative biomarkers couple IFN-γ characteristics with angiogenesis/stromal modules and spatial indicators, offering superior predictive power compared to single tests. These insights support the adoption of a combined strategy: integrating vascular normalization or stromal/myeloid cell reprogramming on the basis of ICB, and encouraging the use of longitudinal “immune snapshots” to guide intervention and precision immunotherapy for renal cancer.